2019
DOI: 10.1186/s13020-019-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of herb-partitioned moxibustion treatment on rats with diarrhea-predominant irritable bowel syndrome

Abstract: Background Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder, which is commonly treated with antidiarrhoeal, antispasmodics, serotonergic agents or laxative agents. These treatments provide relief for IBS symptoms but may also lead to undesired side effects. Previously, herb-partitioned moxibustion (HPM) treatment has been demonstrated to be effective in ameliorating symptoms of IBS. However, the underlying mechanism of this beneficial treatment is yet to be establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…High levels of glucose have been reported in extracts of macroscopically uninvolved colonic mucosa of IBD patients [ 72 ], and also in other biological specimens including fecal extracts in patients with ulcerative colitis [ 73 ]. In support of such a hypothesis, energy-related metabolites in colon appear to be crucial for homeostasis of the gut microbiome and intestinal cells [ 74 , 75 ], and to suggest that increased glucose level in serum samples of the UC rats may be resulting from the disturbance in the host-microbiome system [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…High levels of glucose have been reported in extracts of macroscopically uninvolved colonic mucosa of IBD patients [ 72 ], and also in other biological specimens including fecal extracts in patients with ulcerative colitis [ 73 ]. In support of such a hypothesis, energy-related metabolites in colon appear to be crucial for homeostasis of the gut microbiome and intestinal cells [ 74 , 75 ], and to suggest that increased glucose level in serum samples of the UC rats may be resulting from the disturbance in the host-microbiome system [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics strategies are fully complied with the holistic and multi-target characteristics of TCM 12 and have been successfully applied to explore the biochemical mechanisms of moxibustion therapy in the treatment of irritable bowel syndrome (IBS) 13 , gastric mucosal lesions (GML) 14 , and chronic atrophic gastritis (CAG). 15 Nevertheless, there have been no studies specifically focusing on the metabolic alterations corresponding to moxibustion interventions for AS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicate that moxibustion could affect intestinal microbes [30,31], visceral hypersensitivity [31,32], the brain-gut axis [14,16], gastrointestinal function [33]. Other studies showed the moxibustion or acupuncture have bene t effect for IBS-D by regulating the neuroendocrine system [34], the immune system [35], and other factors.…”
Section: Discussionmentioning
confidence: 99%